Nematode-Trapping Fungi Showed Different Predacity among Nematode Species - Heonil Kang; Insoo Choi; Namsook Park; Changhwan Bae; Donggeun Kim (Research in Plant Disease, 2019)
Nematode-trapping fungi develop trap and consume nematodes are an important part of the subsoil ecosystem and they share a special predator-prey relationship. Four nematode-trapping species, there with adhesive network, Arthrobotrys oligospora, A. sinensis, A. thaumasia and one with constricting ring, Drechslerella brochopaga were collected from soils in Korea and tested their predacity against 12 different nematode species. They were three feeding groups, plant-parasitic (Meloidogyne incognita and Pratylenchus penetrans), fungivorous (Aphelenchus avenae), bacteriovorous (Betlerius sp. and Diplogasteritus sp. in diplogasterid, Panagrolaimus labiatus, P. multidentatus in panagrolaimid, Mesorhabditis irregularis, Pelodera strongyloides and Rhabditis sp., in rhabditid, and Acrobeloides sp. in cephalobid). Results : showed that nematode-trapping fungi successfully captured most of nematodes in Petri dish in the group of plant-parasitic nematodes and rhabditids, moderately and variably in other nematodes in 15 days. But it didn't captured A. avenae and Acrobeloides sp. both belongs to c-p group 2. Numbers of Acrobeloides sp. and A. avenae even increased during the test period. The results of this study indicated that nematode-trapping fungi may have specificity among nematode species.